Psychological and Pedagogical Factors Influencing Choice of Profession - Shoyimova Shoira Sanakulovna (Researchparks Publishing, 2023)
The main questions concerning the identification of psychological and pedagogical factors of professional self-determination of students are considered. The main directions on this issue in modern domestic scientific literature are studied. On the basis of a theoretical analysis, the most significant psychological and pedagogical factors were identified: the student's general knowledge about the profession, his own professional future, the formation of educational and professional motivation, the level of educational and professional activity, etc.